Unruly Bodies: Monstrous Readings of Biotechnology - Verspaget, Cynthia J. (Curtin University, 2015)
This thesis deploys the popular culture figure, the zombie, as a metaphor to examine the intersection of biotechnology and the production of knowledge about the body. Through reference to the HeLa cell line and BioArt project The Anarchy Cell Line, I show how the zombie metaphor helps to analyse and potentially undo Biology’s inflexible binary classification system, allowing a more inclusive and less reductive reading of those who are subject to Biology's system of knowledge.